Animal welfare and farm sustainability in crisis: Hazards of AI in food production - Michnowska, Hanna; Sztandarski, Patryk; Marchewka , Joanna (Crisis Management Days, 2025)
The integration of artificial intelligence (AI) into food production, particularly in response to rising demand for fast-growing, healthy protein sources, presents both opportunities and challenges. Animal producers must navigate issues related to the scale of operations and the substantial resources required to maintain them. With the rise of precision livestock farming (PLF), new hazards have emerged—impacting sustainability, food production, and, critically, farming animal welfare. This article presents a systematic review of literature identifying animal welfare risks associated with AI implementation in farming. It synthetises key concerns to create a crisis management roadmap for large-scale food production systems.